Factors Affecting Customer’s Decision To Saving At Bank Bengkulu Kcp Pasar Kepahiang - Deko Pranata; Ahmad Soleh; Nirta Vera Yustanti (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
The purpose of this study was to determine the effect of location, service quality and product quality on customer’s decisions to save at Bank Bengkulu KCP Kepahiang. The sample in this study was 97 customers who saved at Bank Bengkulu KCP Pasar Kepahiang. Data collection using a questionnaire and the method of analysis used is multiple linear regression, determination test and hypothesis testing. The results of the multiple regression equation show the equation Y = 8.263 + 0.200X1 + 0.392 X2 + 0.227 X3 with a possitive regression direction, meaning that if the location, service quality and the product quality increase, the decision to save will also increase. Location has significant influence on the decision to save at Bank Bengkulu KCP Kepahiang, this evidenced by a significant value of 0.013, less than 0.05. Service quality has a significant influence on the decision to save at Bank Bengkulu KCP Kepahiang, this is evidenced by a significant value of 0.000, less than 0.05. Product quality has a significant influence on the decision to save at Bank Bengkulu KCP Kepahiang, this is evidenced by a significant value of 0.002, less than 0.05. Location, service quality and product quality have a significant effect on the decision to save at Bank Bengkulu KCP Kepahiang, this is evidenced by a significant value of , less than 0.05.